A Novel Approch for Nasal Drug Delivery System - Jadhav, Avinash; Dharashive, Prof.Vishweshwar; Shafi, Dr.Sameer; Chavan, Saiprasad; Honrao, Madhav; Inje , Rahul; Biradar , Akshay (Asian Journal of Pharmaceutical Research and Development, 2024)
The oral route is the most favored technique for administering the drug orally in the body. As a result of certain limitations such as drug absorption, poor bioavailability, first-pass hepatic metabolism and medicine target to particular organs, may cause problems for administration via oral route. Therefore parenteral route, transmucosal route and transdermal route are preferred over oral route. Intranasal route is deemed to be a desirable route because of the time profile of concentration a drug is close to that of the intravenous route. The nasal route has also been successfully used for bypassing the blood-brain barrier and afterword delivering drug molecules to the central nervous system .The in-situ gelling system is a process in which is in a solution form before the administration in the body but it converts in to a gel form after administration . The formation of gel depends on factors like temperature modulation, pH change, presence of ions from which drug get released in sustained and controlled manner. Therefore this review focuses on nasal drug delivery, a variety of aspects of nasal anatomy and physiology, nasal absorption mechanism, and In-Situ gels evaluations.